THU0490 Canakinumab Treatment of Patients with Hyper-IgD Syndrome: An Open-Label, Multicenter, Pilot Study. (23rd January 2014) - Anton, J.; Calvo, I.; Robles, A.; Yagüe, J.; Aróstegui, J.; Viana, R.; Tseng, L.; Abrams, K.
Abstract : Background: Hyper-IgD and periodic fever syndrome (HIDS) is a recessively inherited autoinflammatory disease caused by melavonate kinase ( MVK) gene mutations. It is characterized by recurrent, early-onset, 4-6 days-long acute episodes with fever, lymphadenopathies, rash, headache, abdominal pain, diarrohea, and elevated acute phase reactant. Previous case reports suggest IL-1 blockade as a potential therapy in HIDS and no study data are available with the fully human, selective, anti-IL-1β monoclonal antibody canakinumab (CAN). Objectives: Primary objective was to evaluate if CAN treatment reduces the flare rate in HIDS patients (pts) during a 6-month treatment period (TP), compared with that from a 6-month historical period (HP). Other objectives included changes in key signs/symptoms, and disease control during TP, time to flare after the last CAN dose and safety. Methods: Pts ≥2 yrs old, carrying biallelic MVK mutations, with active disease, C - reactive protein (CRP) >10 mg/L, and ≥3 acute flares in theHP were included. The study included 6- month open-label CAN treatment and a follow-up period lasting until relapse or up to 6 months max. All pts received CAN 4mg/kg (max. 300mg) Q 6 wks in TP, with one permissible dose up-titration to 6mg/kg (max. 450mg), if flare occurred in the first 6 wks. Results: Nine pts (6 females, 3 males) were enrolled from 3 centers. The median age was 17.3 yr (5-29 yr) and the median duration since diagnosis was 4.1 yr (1-25 yr). Median number of flares/patient reduced from 5 (3-12) during HP to 0 (0-2) during the TP. During the TP, only 2 pts had flares (3 in nos.) and the dose was up-titrated in these pts with no subsequent flares thereafter. During the follow-up period 7/9 pts flared, with a median of 110 days (62-196) after the last CAN dose. At baseline, the physician rated 6 and 3 pts as having no and poor disease control, respectively. Beginning at Day 4, all pts were rated as having good or excellent disease control. At baseline 8/9 had moderate to severe fever, 8/9 had mild/moderate lymphadenopathy, 5/9 had mild/moderate abdominal pain and 4/9 had mild/moderate apthous ulcers. From Day 4 onwards, no patient had fever or abdominal pain, and only one had mild to moderate lymphadenopathy and apthous ulcers. At baseline, the median levels of CRP and serum amyloid protein (SAA) were elevated (117.7 mg/L and 627 mg/L, respectively). Both the levels normalized by Day 15 (CRP: 0.8 mg/L; SAA: 2.6 mg/L) and remained so for the remainder of the trial. Only transient elevations were detected during acute flares. Eight pts had at least one adverse event (AE). Most were of mild (76%) or moderate (18%) severity, and infections, mostly involving the respiratory tract, were the most common type. Two pts reported a serious AE (1 with HIDS flare, and 1 with a gastrointestinal bleed and separate peritonitis). No AEs led to discontinuation. Conclusions: In this study, CAN treatment substantially reduced the HIDS flare rate. Both physicians and pts felt that the disease was under good/excellent control during CAN treatment. The AEs reported were manageable. Further study is needed to better define CAN treatment in HIDS. Disclosure of Interest: J. Anton: None Declared, I. Calvo: None Declared, A. Robles: None Declared, J. Yagüe: None Declared, J. Aróstegui: None Declared, R. Viana Employee of: Novartis, L. Tseng Employee of: Novartis, K. Abrams Employee of: Novartis